ANALISIS BELUM OPTIMALNYA REALISASI ANGGARAN BELANJA PADA BAGIAN UMUM SETDA MALUKU - Jaelani La Masidonda; Muslim Muslim; Ayun Karmila Nursan (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2021)
This study aims to analyze the not yet optimal realization of the expenditure budget at the Maluku Regional Secretariat General Bureau. This study uses a quantitative descriptive research approach and is supported by in-depth interviews, in which the researcher explains existing phenomena using numbers to obtain an overview and characteristics of the conditions under study. Data collection is done by means of interviews, observation (observation) and documentation. Data analysis techniques use spending variance and spending growth. The results of this study indicate that the results of the analysis of variance on state spending in 2019 - 2020 show an increase. Meanwhile, the results of the analysis of budget growth in 2020 show not good. This is because the growth value is negative, which is caused by refocusing. Keywords: Analysis, Budget, Expenditure Realization